2008
DOI: 10.1182/blood-2007-05-090928
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the chemokine (C-X-C motif) ligand 10 are associated with invasive aspergillosis after allogeneic stem-cell transplantation and influence CXCL10 epression in monocyte-derived dendritic cells

Abstract: Patients after allogeneic stem-cell transplantation (alloSCT) have an increased risk for invasive aspergillosis (IA). Here, recipients of an allograft with IA (n ‫؍‬ 81) or without IA (n ‫؍‬ 58) were screened for 84 single nucleotide polymorphisms in 18 immune relevant genes. We found 3 markers in chemokine (C-X-C motif) ligand 10 (CXCL10, 4q21, 11 101 C > T, P ‫؍‬ .007; 1642 C < G, P ‫؍‬ .003; ؊1101A < G, P ‫؍‬ .001) significantly associated with an increased risk of developing IA. Furthermore, immature dendr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
67
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 21 publications
7
67
1
1
Order By: Relevance
“…In the present study we found significant changes in the levels of TNF-␣, CXCL10, and CCL2, all of which are significant mediators of inflammation during IPA infection. TNF-␣ plays an important role in the recruitment of neutrophils, CXCL10 promotes dendritic cell and macrophage recruitment, and CCL2 acts as a chemoattractant for macrophages (38,50). In our studies, we found that all three of these factors were decreased in TLR9 Ϫ/Ϫ mice at day 2 after challenge with resting conidia but increased in TLR9 Ϫ/Ϫ mice at day 4 after challenge with swollen conidia.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…In the present study we found significant changes in the levels of TNF-␣, CXCL10, and CCL2, all of which are significant mediators of inflammation during IPA infection. TNF-␣ plays an important role in the recruitment of neutrophils, CXCL10 promotes dendritic cell and macrophage recruitment, and CCL2 acts as a chemoattractant for macrophages (38,50). In our studies, we found that all three of these factors were decreased in TLR9 Ϫ/Ϫ mice at day 2 after challenge with resting conidia but increased in TLR9 Ϫ/Ϫ mice at day 4 after challenge with swollen conidia.…”
Section: Discussionsupporting
confidence: 46%
“…Investigations in the area of innate immune receptors and soluble factors that inhibit or enhance immune activation during IPA or ABPA have led to considerable progress in understanding its underlying mechanisms. In particular, inflammatory cytokines and chemokines such as tumor necrosis factor alpha (TNF-␣) (36,40,46), CCL2 (6), and CXCL10 (38) play critical roles in the activation and recruitment of immune cells such as dendritic cells and macrophages that further act to regulate inflammation at the site of Aspergillus infection. More recently, interleukin-17 (IL-17) has also been demonstrated to promote inflammation and infection during Aspergillus infection (58).…”
mentioning
confidence: 99%
“…Ϫ/Ϫ chimeric mice produced significantly higher CXCL10, a chemokine recently shown to render the host susceptible to invasive aspergillosis if inappropriately expressed (31). Additionally, both wild-type and CCR7 Ϫ/Ϫ chimeras showed similar expression of the potent antiinflammatory cytokine IL-10 after conidia challenge.…”
Section: Discussionmentioning
confidence: 75%
“…Although it is not immediately clear why CXCL10 and CXCL9 were increased in the CCR7 Ϫ/Ϫ chimeric mice, it has been reported that high levels of CXCL10 correlate with decreased susceptibility to IA. 41 Thus, the balance of pro-and anti-inflammatory mediators produced in the CCR7 Ϫ/Ϫ 3WT chimeras after infection appears to enhance fungal clearance.…”
Section: Discussionmentioning
confidence: 99%